2014
DOI: 10.1097/dss.0000000000000057
|View full text |Cite
|
Sign up to set email alerts
|

Combination Treatment of Low-Fluence 1,064-nm Q-Switched Nd

Abstract: Our results suggest that the combination of the IPL-F with LF-QS-Nd:YAG laser may be an effective and safe modality for melasma patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The number of required treatments is generally more than those for other light- and laser-based treatment modalities. Several recent studies suggest that fractionating the laser energy (Yue et al, 2016) or combining low-fluence Q-switched lasers with long-pulsed Nd:YAG (laser toning [Kang et al, 2011] or IPL [Vachiramon et al, 2015, Yun et al, 2014]) may reduce the recurrence rate. However, until the recurrence rate is reduced significantly in a reproducible way and the relatively high rates of posttreatment dyspigmentation are resolved, Q-switched laser therapy for patients with melasma is likely reserved for very recalcitrant cases that have failed with other laser modalities first.…”
Section: Overview Of Laser- and Light-based Treatment Optionsmentioning
confidence: 99%
“…The number of required treatments is generally more than those for other light- and laser-based treatment modalities. Several recent studies suggest that fractionating the laser energy (Yue et al, 2016) or combining low-fluence Q-switched lasers with long-pulsed Nd:YAG (laser toning [Kang et al, 2011] or IPL [Vachiramon et al, 2015, Yun et al, 2014]) may reduce the recurrence rate. However, until the recurrence rate is reduced significantly in a reproducible way and the relatively high rates of posttreatment dyspigmentation are resolved, Q-switched laser therapy for patients with melasma is likely reserved for very recalcitrant cases that have failed with other laser modalities first.…”
Section: Overview Of Laser- and Light-based Treatment Optionsmentioning
confidence: 99%
“…Another article has been excluded because this has been retracted from PubMed. [ 84 ] Finally, 10 studies evaluated LFQS Nd:YAG laser on 446 patients[ 85 86 87 88 89 90 91 92 93 94 ] [ Table 11 ].…”
Section: Chemical Peelsmentioning
confidence: 99%
“…One study treated 12 patients with fractionated IPL (IPL-F) and low-fluence (LF) QS-1,064 nm Nd:YAG laser therapy and compared the MASI scores to those of 12 patients who underwent the same number of treatments with IPL-F alone. This study found a greater improvement in the combination treatment group than those who were treated with IPL-F alone ( Yun et al, 2014 ). Combination CO 2 laser therapy in combination with QS-alexandrite (alex) laser therapy showed better results than therapy with QS-alex alone but was associated with more frequent adverse effects ( Angsuwarangsee and Polnikorn, 2003 ).…”
Section: Melasmamentioning
confidence: 72%